Legal Safeguards for Victims of Data Dissemination Crimes and Cybercrime Protection - Enggarsasi, Umi; Sa’diyah, Nur Khalimatus; Martio, Pratama Alifiandi (Unissula, 2024)
In the digital age, legal protections for personal data are insufficient, leaving individuals vulnerable to financial losses from data theft and criminal dissemination of personal information. This research focuses on assessing the effectiveness of existing regulations, such as Law Number 27 of 2022 Concerning Personal Data Protection. Employing an empirical juridical approach for field research and a conceptual approach for theoretical analysis. The analysis underscores that personal data, crucial for identification, is a frequent target for malevolent actors seeking financial gain, leading to profound consequences for victims. Incidents of personal data theft, often orchestrated by fraudsters, extend beyond financial losses, compromising personal information available for purchase on clandestine online platforms like the dark web. Despite existing regulations, the research identifies a significant gap in providing clear guidelines for safeguarding individuals in the digital era. The study concludes that the current legal framework, while foundational, requires a more comprehensive focus on the Personal Data Protection Law due to inherent weaknesses. This research contributes valuable insights into the evolving legal landscape surrounding personal data crimes in Indonesia, ensuring a comprehensive understanding of legal protections for victims amidst technological advancements.